2020
DOI: 10.1016/j.ymssp.2020.106753
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic emission activity detection method based on short-term waveform features: Application to metallic components under uniaxial tensile test

Abstract: The Acoustic Emission (AE) phenomenon has been used as a powerful tool with the purpose to either detect, locate or assess damage for a wide range of applications. Derived from its monitoring, one major current challenge on the analysis of the acquired signal is the proper identification and separation of each AE event. Current advanced methods for detecting events are primarily focused on identifying with high accuracy the beginning of the AE wave; however, the detection of the conclusion has been disregarded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…At first, by totaling the number of detected signals versus the correct positions (referring to a total amount of true signals presenting in the data frame), classify the properly detected signals (true positive), missed signals (false negative) and mistake detected signals (false positive). Then, these indicators are obtained: accuracy (ACC, the ratio of true-positive detections against to all detected and not detected signals); false-discovery rate (FDR, the ratio of false-positive detections to the whole detected signals); false-negative rate (FNR, the ratio of false-negative detections to the sum of false-negative detections and true positive detections); and the F1-score (the harmonic of 1-FNR and 1-FDR) [34]. Then, these indicators are obtained: accuracy (ACC, the ratio of true-positive detections against to all detected and not detected signals); false-discovery rate (FDR, the ratio of false-positive detections to the whole detected signals); false-negative rate (FNR, the ratio of false-negative detections to the sum of false-negative detections and true positive detections); and the F1-score (the harmonic of 1-FNR and 1-FDR) [34].…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…At first, by totaling the number of detected signals versus the correct positions (referring to a total amount of true signals presenting in the data frame), classify the properly detected signals (true positive), missed signals (false negative) and mistake detected signals (false positive). Then, these indicators are obtained: accuracy (ACC, the ratio of true-positive detections against to all detected and not detected signals); false-discovery rate (FDR, the ratio of false-positive detections to the whole detected signals); false-negative rate (FNR, the ratio of false-negative detections to the sum of false-negative detections and true positive detections); and the F1-score (the harmonic of 1-FNR and 1-FDR) [34]. Then, these indicators are obtained: accuracy (ACC, the ratio of true-positive detections against to all detected and not detected signals); false-discovery rate (FDR, the ratio of false-positive detections to the whole detected signals); false-negative rate (FNR, the ratio of false-negative detections to the sum of false-negative detections and true positive detections); and the F1-score (the harmonic of 1-FNR and 1-FDR) [34].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…It can be observed that on average, the proposed method is superior to the better reference in terms of the ACC (46.31%), FDR (6.16%), FNR (48.59%) and F1-score (34.36%) due to the accurate adaptability of the threshold calculated by statistical commonality of the complex urban noise, and the bottleneck problem for current methods of calculating the threshold separating signals and environmental noise accurately without affecting the integrity of signal is solved. Figure 9 gives an example of the manual determination of the onset and the endpoint of the actual signal with the wavelet synchrosqueezed transform (WSST) method, which are chosen as the actual onset and the actual endpoint of actual signal [34], and the error calculations of the onset and endpoint are the same as the simulated data stream. Due to the limitation of the number of correct detections by the LSFM method, 100 samples are collected to calculate the errors of the onset and endpoint for a kind of signal shown in Figure 10.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…e acoustic emission (AE) phenomenon has been used as a powerful tool with the purpose to either detect, locate, or assess damage for a wide range of applications [37]. Deformation and crack propagation of materials under stress are important mechanisms of structural failure.…”
Section: Principle Of Acoustic Emission Detectionmentioning
confidence: 99%
“…A change in the AE phenomenon increases the energy of the AE signal detected by the AE sensors in the form of hits. These hits can be overwhelmed by interference noises [31]. Continuous wavelet transform (CWT) can be used to analyze leak-related useful hits.…”
Section: Introductionmentioning
confidence: 99%